Changes in patterns of treatment of burned children at the Linkoping Burn Centre, Sweden, 2009–2014. Issue 5 (August 2017) - Elmasry, Moustafa; Steinvall, Ingrid; Abdelrahman, Islam; Olofsson, Pia; Sjoberg, Folke
Highlights: Children are a large group among patients with burns in Sweden. Retrospective analysis of burned children in the period between 2009/2015. Flexible outpatient treatment is the promising area for future development. Abstract: Introduction: Children are a relatively large group among patients with burns in Sweden. We changed the management of children's burns to a flexible, outpatient-based plan. The aim was to follow up the outpatient management for children's burns during the period 2009–2014, and track it, to find out to what extent the patients had been treated flexibly as outpatients, and to clarify the reasons behind those who did not fit in the plan. Methods: Descriptive retrospective analysis dividing the patients into three groups: inpatients only, flexible management, and outpatients. Other variables recorded included: age, sex, percentage total body surface area burned (TBSA%), percentage full thickness burn (FTB%), cause of burn, county of residence, operations required, number of visits to the outpatient department, costs, and duration of overnight stay in the hospital. Results: The study group included 620 children: nine were managed strictly as inpatients, 204 as flexible outpatients, and 407 strictly as outpatients. Among the total there were 269 children who came from remote areas (43%), and of these 260 were treated as outpatients and flexible outpatients. Median TBSA% in the whole group was 1 (10th–90th centile 0–9) with the biggest median TBSA% 12 (5–38) in the inpatient group. The most common cause of injury was scalds (332/620, 54%). Costs/patient (US) was lower in the flexible outpatient group than in the inpatient group (median 10 557 (3213–35 802) and 35 343 (7344–66 554), respectively). Conclusion: Based on the results, we expect that the flexible outpatient treatment plan for children with minor to moderate burns can be expanded in the future. The results encourage us to continue the service and to further reduce duration of stay in hospital below the level already achieved (25% of the whole period of care).